Generasi Muda dan Estafet Kepemimpinan Islam Masa Depan - Nosy Restia; Ahmadi, Ahmadi (Edumulti: Jurnal Rumpun Ilmu Pendidikan Multidisiplin, 2025)
This study aims to examine the strategic role of youth in the future succession of Islamic leadership. Using a qualitative method through library research, the study emphasizes the importance of integrity, spirituality, and innovation in shaping young leaders capable of addressing contemporary challenges. The findings reveal that the millennial generation holds significant potential as agents of social change through inclusive, adaptive, and transformational leadership. Their interest in entrepreneurship and the use of digital technology serves as a key asset in actualizing Islamic values within society. An integrative leadership model combining spiritual, intellectual, social, and emotional aspects is deemed essential in developing young leaders who can bridge Islamic principles with global dynamics. This study contributes both theoretically and practically to the advancement of Islamic leadership rooted in youth empowerment.